Interpretação do espaço urnbano de Maringá : a lógica da verticalização - período de 1990 a 2005 - Giménez, Humberto Marshal Mendes (2007)
This study analyzes the vertical growth process in Maringá-PR, that is taking place in an enclosed area at traditional center calls "New Center", more specifically, originated from the removal of the rail station and the patio of maneuvers place, as well as of the lowering of the rails. The area has largely been used for the vertical growth, what has caused an interesting urban process in the city. The vertical growth begins to make real when the economy in the country is modernized and the capitalism moves forward. As the space, the earth and the lodging in a capitalist society follow a capitalist logic, the vertical growth should also be understood inside of that logic. It interferes in the capitalist context through the valorization of the earth. In that sense, according to Souza (1994, p. 173) "there is no way to deny that the vertical growth geography corresponds with a geography of the valorization, clearly coupled, in its expansion process, to the infrastructure availability, due to which the poor people are permanently repelled." In that process the segregation happens. For segregation is understood a concept that is expressed in a space way, establishing zonings that end for to divide and to split up the population, each fraction in its homogenized space. The North Parana development, based on the agriculture of coffee mainly and modernized plantations destined to the export later, linked to the agribusiness, has been accumulating the necessary capital to undertake the referred process. In the 80's happened a true vertical growth explosion in Maringá. However in the 90's, by political and economical changes, the vertical growth has been configured in a more modest and quite several way, what has continuity in this XXI century beginning. The number of buildings radically decreased, the constructions nature and its aiming public have also been presenting changes. The price is quite high and the units are small for singles or students. The New Center is considered an incorporate area to the center with reproduction objectives of capital and of realestate speculation. This area began to be built after intense conflicts and pressures about the public power being constituted in an urbanization of the possible